Westdene: a suburban densification - transforming Westdene from a non-place to a place - Van der Merwe, M (My University, 2021)
The research report, Westdene: A suburban densification, investigates how a residential precinct can appropriately develop over time from plot scale to precinct scale. Westdene has a contrasting set of characteristics: it is historic with a youthful influence, residential but on the precipice of densifying with permanent residents and a need for increased student and social housing. Despite the existing infrastructures, and upgrades thereof, Westdene has become dilapidated and seldomly used mainly due to low density, a lack of attractions and the haphazard densification of buildings. As a result Westdene has become a means by which you access another destination rather than a destination in itself. Th is begs the question as to how current research on ‘best practice’ densification can inform strategies for the localization of Westdene as a case of a historically significant first ring suburb. The investigation started by observing the irregularities of natural densification in the precinct and its effect as noted by the lack of architectural continuity and progressive loss of residential character. Natural densification occurs on a plot scale before multiplying into an eventual precinct plan. The research will employ an existing design methodology developed by Ian McHarg to the selected area by mapping existing, observable site informants and subsequently responding to these informants. The idea is to replicate the proper design codes onto a specific typology. Private developers and residents of the neighbourhood can then densify as needed within design parameters and good urban design principles. The idea is not to remove the autonomy of the inhabitants, but rather to guide them when they embark on future densification ventures by creating a space that is both functional, leaves potential for growth and garners interest in its visitors as an option for possible long term habitation
A research report submitted in partial fulfillment of the requirements for the degree of Master of Urban Design, (MUD), to the Faculty of Engineering and the Built Environment, University of Witwatersrand, 2021